The dietary effects of DL- and L- methionine on broiler chicken growth performance, carcass composition and intestinal villi height and crypt depth - Zainudin, Mohamad Amirul Asyraf (2017)
This study was conducted to determine the dietary effect of DL- and L-Methionine on growth performance, carcass composition and intestinal villi height and crypt depth of broiler chicken. The study was conducted on five hundred and sixty Cobb 500 day old chicks raised for 35 days. The chicks were divided into four dietary treatments groups; each treatment had 7 replicate containing 20 chicks per replicate. Basal diet was formulated with corn and soybean at two stages; starter and finisher. Each treatment was supplemented with different level of DL- and L-Methionine. The level was 0.350% and 0.264% for starter while 0.260% and 0.179% for finisher. There is no significant difference found for growth performance especially feed conversion ratio (FCR) for each of the type and level of DL-Met and L-Met. For carcass composition, no significant result (P > 0.05) was found for each of the treatment. No significant interaction (P > 0.05) had be found between the type and level DL-Met and L-Met. Usage of different type and level of methionine showed significant result (P < 0.05) on the villus height of jejunum and ileum as well as crypt depth for jejunum. There was no significant result (P > 0.05) for villus height of duodenum and crypt depth of duodenum and ileum. Overall, there was no significant effect (P > 0.05) between the type and level of DL-Methionine and L-Methionine on the villi height and crypt depth.